Recent Advances in the Synthesis of 2,2′-Bipyridines and Their Derivatives - Rubtsov, Aleksandr E.; Malkov, Andrei V. (Synthesis, 2021)
The sustained interest in the synthesis of new analogues of 2,2′-bipyridines is supported by the importance of compounds featuring bipyridine core in diverse areas of chemical, biomedical and materials research, which is relayed into the development of new approaches and the expansion of existing synthetic methods. This short review covers advances in the synthesis of 2,2′-bipyridines, including both the synthesis of compounds with a given substitution pattern and the development of new methods for assembling the bipyridine core. Special attention is directed toward the use of pyridine N-oxides and metal-free protocols to facilitate the formation of bipyridines. This short review focuses primarily on reports published in the last 5–6 years.1 Introduction2 Ullmann-Type Homocoupling Reactions3 Cross-Coupling Reactions in the Synthesis of Bipyridines4 Coupling Reactions Employing Pyridine N-Oxides5 Other Methods for the Synthesis of 2,2′-Bipyridines6 Conclusions and Outlook
Keywords: bipyridines; cross-coupling; catalysis; oxidative dimerization; C–H activation; regioselectivity; chemoselectivity